Industrial growth in the Cordillera Administrative Region an economic base analysis - Diaz, Marion Jezelle C.; Yambao, Ludy Ann L. (2013)
This study uses three techniques to determine industries that generate economic growth in the region using current employed data contrasted with employment data on older than seven years prior.The location quotient analysis is used to determine the basic sectors which according to the economic base theory are the engine of the local economy. This will determine industries that drive the local economy by creating outside income for the region. Second is the shift-share analysis which is used to analyze the economy of CAR by comparing how well the region grew relatively to its national counterpart. It strengthens the economic base analysis by providing the analysis with a reference point to compare with the local economy. Third is the industry targeting and leading-lagging analyses which are used to classify the economic performance of each industry in CAR. This will help determine industries int the region that are considered high, medium or low growth prospects. The result of the study show that the top industries that drive the economy of CAR are mining and quarrying, electricity, gas, and water, and education. This is consistent with expectations because of the region's topography as well as the natural and human resources present in the area which are naturally suited for such industries. Meanwhile, industries like agriculture, hunting and forestry and manufacturing were shown to perform poorly -- Author's abstract.